2016
DOI: 10.1089/ars.2015.6315
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Attenuates Inflammatory Hepcidin by Reducing IL-6 Secretion and Promoting SIRT1-Mediated STAT3 Deacetylation

Abstract: Aims: Anemia of inflammation is quite prevalent in hospitalized patients with poor prognosis. Concerns about the effectiveness and safety of iron supplementation have arisen, driving the demand for alternative therapies. Induction of hepatic hepcidin, the master hormone of iron homeostasis, causes anemia under inflammatory conditions. Previous studies indicated that hydrogen sulfide (H 2 S), the third gasotransmitter and a well-known regulator of inflammation, may inhibit the secretion of inflammatory cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 59 publications
3
52
1
Order By: Relevance
“…SIRT1 plays a significant role in the deacetylation of NF‐ƙB, which resulted in a decrease in proliferation proteins such as CyclinD1 and PCNA . Additionally, SIRT1 has been shown to downregulate STAT3 and reduced reactive astrogliosis . In this study, we observed a significant reduction in endogenous SIRT1 expression along with an increase in cell proliferation marker CyclinD1 after GMH.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…SIRT1 plays a significant role in the deacetylation of NF‐ƙB, which resulted in a decrease in proliferation proteins such as CyclinD1 and PCNA . Additionally, SIRT1 has been shown to downregulate STAT3 and reduced reactive astrogliosis . In this study, we observed a significant reduction in endogenous SIRT1 expression along with an increase in cell proliferation marker CyclinD1 after GMH.…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies have demonstrated that SIRT1 plays an essential role in cell proliferation and cell survival . SIRT1 attenuates reactive astrogliosis by targeting nuclear factor ƙB (NF‐ƙB) and signal transducing activator of transcription 3 (STAT3) . Thus, IL‐17A activation of the IL‐17RA/C/EBPβ signaling pathway may play a role in reactive astrogliosis, whereas SIRT1 signaling pathways attenuate reactive astrogliosis after GMH.…”
Section: Introductionmentioning
confidence: 99%
“…The IL6 antibody Siltuximab lowered hepcidin and improved anemia in patients with multicentric Castleman’s Disease [52]. Hydrogen sulfide suppressed hepcidin and improved hypoferremia in LPS-treated mice by suppressing IL6 production and promoting sirtuin 1-mediated deacetylation of STAT3 to inhibit its activity [53]. …”
Section: Novel Therapeutic Strategies For Aimentioning
confidence: 99%
“…For example, H 2 S upregulated SIRT1 to inhibit endoplasmic reticulum stress in PC12 cells [67] and to prevent H 2 O 2 -induced [68] or nicotinamide-induced [69] senescence in human umbilical vein endothelial cells (HUVECs). Besides HUVECs, previous studies from our group demonstrated that H 2 S increased SIRT1 expression to abolish the oxidative stress induced apoptosis in H9c2 cardiomyocytes [70] and previous studies from our group demonstrated [6] found that H 2 S attenuated inflammatory hepcidin partially by promoting SIRT1-mediated STAT3 deacetylation. SIRT3, one of the isoforms of SIRT family, has also been reported that it could be regulated by H 2 S to protect endothelial cells in an antioxidant manner [71].…”
Section: H2s Epigenetic Regulation Atherosclerosis Is An Important Famentioning
confidence: 82%
“…CSE is generally located in cardiovascular system [5], liver [6], kidney [7] and gastrointestinal tract [8-10]. CBS protein expression is dominant in the brain [11], and its existence in other tissue has been confirmed (e.g., liver, kidney, uterus and gastrointestinal tract [12-14]).…”
Section: H2s Production and Eliminationmentioning
confidence: 99%